Respect for the court as one of the principles of a legal state - Kravchuk, Valentina; Stashkіv, Nadiia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the research of the respect to the court as a factor in the proper functioning of a legal state. It is established that a strong, authoritative, independent and protected court is one of the principles of a legal state; respect for the judicial power is a guarantee of its stability. Strengthening the guarantees of independence and building respect for the judiciary, increasing its authority, sureness in its uprightness, independence and objectivity ensures the effective justice, guarantees stability, peace and tranquility in the state